Rwanda : Poverty Reduction Strategy Paper; Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This paper reviews the Annual Progress Report for Rwanda's Poverty Reduction Strategy Paper (PRSP). The performance of the Rwandan economy improved in 2004. GDP growth increased from 0.9 percent to 4.2 percent. The Government of Rwanda continued the implementation of its widespread program of reform of the national public finance management system. Progress on aid coordination and harmonization was consolidated during 2004 by putting in place some new structures, such as the External Finance Unit in Ministry of Finance and Economic Planning and the Development Partners Coordination Group secretariat.